Women and girls in the Hindi public sphere periodical literature in colonial North India - Nijhawan, Shobna (New Delhi ; Oxford : Oxford University Press, 2012)
An in-depth study of Hindi women's periodicals in early 20th century north India, this volume investigates debates around gender roles, the politicisation of women, and language politics as they were presented to a primarily female audience during a period of social reform and heightened nationalist activism.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Women in mass media; Hindu women -- India; Women's periodicals; Periodicals -- Publishing -- India, North -- History -- 20th century